The prevalence and related factors of pre‐diabetes and diabetes among overweight and obese children in Urban schools - Kisokanth G; Indrakumar J; Arulpragasam AN; Ilankoon IMPS (Medsci Publications, 2022)
Objective: This study aimed to determine the prevalence of pre‐diabetes and diabetes among overweight and obese children in urban schools and factors associated with them, in Batticaloa District, Sri Lanka. Methods: A school based cross‐sectional descriptive study was conducted to collect data on socio-demographic information, eating habits and physical activities, using a validated, pre-tested questionnaire. In addition, anthropometric measurements and glycosylated haemoglobin (HbA1c) test were performed. Multivariate logistic regression analyze was performed to identify the factors associated with glycemic status by using SPSS v23. Results: Out of the 269 children recruited, 59% were obese. Prevalence of pre‐diabetes (HbA1c 5.7%-6.4%) and diabetes (HbA1c ≥ 6.5%) were 20.1% (95% CI 15.5%-25.4%) and 3.3% (95% CI 1.5%-6.3%) respectively. Multivariate regression shows that having a BMI of ≥ 27.5Kg/m2 (AOR=2.69), male gender (AOR=2.71) and ethnicity (AOR = 2.58) were found to be significant factors for higher HbA1c (≥5.7%). Conclusions: Prevalence of prediabetes and diabetes among overweight and obese school children was high and mainly associated with body weight which is a modifiable risk factor. Lifestyle modifications focusing on weight reduction among overweight and obese school children especially boys, need to be carried out.